Association of peripartum troponin I levels with left ventricular relaxation in women with hypertensive disorders of pregnancy. Issue 2 (12th September 2018) - Umazume, Takeshi; Yamada, Satoshi; Yamada, Takahiro; Ishikawa, Satoshi; Furuta, Itsuko; Iwano, Hiroyuki; Murai, Daisuke; Hayashi, Taichi; Okada, Kazunori; Morikawa, Mamoru; Tsutsui, Hiroyuki; Minakami, Hisanori
Abstract : Objective: Women with hypertensive disorders of pregnancy (HDP) show elevated risk of heart failure despite decreased circulating plasma volume compared with those with normotensive control pregnancies (NCP). This study was performed to better characterise the heart in women with HDP and determine whether high-sensitivity troponin I (hs-TnI) around childbirth predicts reduced left ventricular (LV) relaxation at 1 month postpartum. Methods: Echocardiography was performed longitudinally during the first, second and third trimesters and immediately postpartum within 1 week and 1 month postpartum in 24 women with HDP, with simultaneous determination of blood variables in comparison with 51 women with NCP. Results: Compared with NCP, HDP showed greater antepartum left atrial (LA) volume, LV mass and inferior vena cava (IVC) diameter, higher peripartum brain natriuretic peptide/N-terminal pro–B-type natriuretic peptide and hs-TnI with the highest value immediately postpartum, and lower early diastolic mitral annular velocity (e') during pregnancy/postpartum. In analyses of data on HDP and NCP, hs-TnI at the third trimester as well as that immediately postpartum was negatively correlated with later e' at 1 month postpartum. The areas under the receiver operating characteristic curves were 0.82 and 0.81 for hs-TnI at the third trimester and immediately postpartum, respectively, in the prediction of reduced LV relaxation at 1 month postpartum. Conclusion: Reduced LV diastolic function and decreased splanchnic blood reservoir may contribute to the increased third trimester IVC diameter and LA volume in women with HDP. The rise in hs-TnI around childbirth was associated with poor LV relaxation ability at 1 month postpartum.